Struggling with destiny in Karimpur, 1925-1984 - Wadley, Susan Snow, 1943- (University of California Press, 1994)
Susan Wadley first visited Karimpur--the village "behind mud walls" made famous by William and Charlotte Wiser--as a graduate student in 1967. She returned often, adding hears of changes in agriculture, labor relations, education, and the family. But Karimpur's residents do not speak with one voice in describing the ways their lives have changed--viewpoints vary considerably depending on the speaker's gender, economic status, and caste. Using cultural documents such as songs and stories, as well as data on household budgets and farming practices, Wadley examines what it means to be poor or rich, female or male. She demonstrates that the forms of subordination prescribed for women are paralleled by those prescribed for lower castes
Keywords: Ethnology -- India -- Mainpuri (District); Villages -- India -- Mainpuri (District); Families -- India -- Mainpuri (District); Social change -- India -- Mainpuri (District); Mainpuri (India : District) -- Social conditions.; Mainpuri (India : District) -- Rural conditions.; Villages.; Ethnologie -- Inde -- Mainpuri (District); Villages -- Inde -- Mainpuri (District); Familles -- Inde -- Mainpuri (District); villages.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; SOCIAL SCIENCE / Anthropology / Cultural & Social; Ethnology; Families; Rural conditions; Social change; Social conditions; Villages; India -- Mainpuri (District); Dorf; Sozialer Wandel; Uttar Pradesh; Karimpur; Agrarische maatschappij.; Sociaal-economische verandering.; Villages -- Inde -- Mainpuri (district); Changement social -- Inde -- Mainpuri (district); Famille -- Inde -- Mainpuri (district); Mainpuri (Inde; district) -- Conditions sociales.; Social conditions -- History; Uttar Pradesh (India)